The Thinking Of Islamic Education Renewal In The Perspective Of Mr. Haji Sulong Al-Fathoni - Zailani Z; Abu Bakar Karsae (UMSU, 2018)
This research discusses the thoughts about educational renewaldone by Haji Sulong. The purpose of this study was to find out the background of Haji Sulong in reforming Islamic education in Patani and the concept of renewing the thought of Haji Sulong Islamic education in Patani. This type of research is qualitative literature research. in this study, the authors used data from other authors as a source of data. The data was collected using literature study techniques, data collection techniques were carried out through library and documentation studies, namely studying books and written materials. The type of research shows the concept championed by Haji Sulong in the renewal of Islamic education in Patani is by developing the Pondok education system into a madrasah education system. The renewal was realized by initiating the establishment of Madrasah al-Ma'arif al-Wathoniyah in Patani